Communication dimension of a Facebook group: first-hand experience from an EAP class - Juraj Datko (Educational Role of Language Journal, 2020)
The paper analyses student-teacher and student-student interactions in a Facebook group that was created as an alternative learning management system (LMS) for an English for Academic Purposes (EAP) course. Our case study is based on students’ perceptions and opinions reconstructed from interviews and diaries and uses traceable objective data from the Facebook group as a complement. The research sample includes thirty-four undergraduates. Our results indicate that Facebook group is perceived as an effective communication channel due to various reasons such as immediacy of feedback or peer interactions outside the language class. Based on our findings, we formulate recommendations for practice.